Improving the validity of estimates of mortality inequalities by education in England & Wales - Gerry McCartney (Population Health Metrics)
Abstract Health inequalities are an important societal injustice. Understanding their scale and trends, and how they compare internationally, is needed to inform policy and practice, and also in order to evaluate the impacts of different policies. Many studies comparing health inequality trends across Europe have used educational attainment as a means of ranking adult populations, but there have been challenges as a consequence of the educational attainment data being missing, or categorising a very large proportion of the total population into a single group. Janssen et al. have recognised this challenge and have proposed an innovative and helpful method to overcome the problems of missing data. Although these are useful improvements, they still leave > 80% of the population categorised in the same group for some years, limiting the validity of the inequality measure.